2012
DOI: 10.1016/j.socscimed.2012.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Social network type and health-related behaviors: Evidence from an American national survey

Abstract: This study examined the association between social network type and engagement in physical activity, alcohol abuse and use of complementary and alternative medicine by older Americans. Data from the National Social Life, Health & Aging Project were employed. Multivariate logistic regressions conducted separately for each health behavior showed that older people embedded in less resourceful network types were at greater risk for alcohol abuse, physical inactivity and less use of complementary and alternative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 37 publications
6
88
0
Order By: Relevance
“…Overall, our findings indicate that among the general population of older English adults, social isolation, but not loneliness, might have consequences for longer term patterns of health-related behaviors. Our findings are consistent with studies that have found relationships between social isolation and physical activity, diet, smoking, and obesity [20,[33][34][35]37,39] but inconsistent with those finding patterns of alcohol abuse and abstinence to be associated with isolation [36,40]. Our results are also consistent with other findings using the ELSA data, which found that social isolation (defined according to marital status, rather than living alone) was prospectively associated with declines in physical mobility and cognitive function, and risk of all-cause mortality [9,15,61].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Overall, our findings indicate that among the general population of older English adults, social isolation, but not loneliness, might have consequences for longer term patterns of health-related behaviors. Our findings are consistent with studies that have found relationships between social isolation and physical activity, diet, smoking, and obesity [20,[33][34][35]37,39] but inconsistent with those finding patterns of alcohol abuse and abstinence to be associated with isolation [36,40]. Our results are also consistent with other findings using the ELSA data, which found that social isolation (defined according to marital status, rather than living alone) was prospectively associated with declines in physical mobility and cognitive function, and risk of all-cause mortality [9,15,61].…”
Section: Discussionsupporting
confidence: 69%
“…Among older adults, social isolation has been associated with having a poor diet [33,34], being physically inactive [20,[34][35][36], problematic consumption of alcohol [34,36,37], and smoking [34,37]. In the Framingham Heart Study, obesity and heavy alcohol consumption have been shown to spread through family and friend networks over time, but so have positive behaviors related to substance use including smoking cessation and alcohol abstinence [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…92 There was well-established evidence that the characteristics of an individual's personal social network can impact on health behaviours and outcomes, through various mechanisms that may include social influence, sense of control and perceived support. 93 The influence of social network contacts such as family and friends can directly impact health-related behaviours such as use of health services, 94 while network typologies had been developed to show that resourceful networks are linked to lower alcohol abuse and higher physical activity. 95 We also noted that the quality of social relationships rather than the number of ties may provide a better indicator of well-being; not all social ties are positive and supportive.…”
Section: The Recovery Approachmentioning
confidence: 99%
“…Scholars who have examined qualitative aspects of older adults' convoys have identified network types based on relationship quality patterns, including: high quality network, high family/friend quality, high spouse/family quality, low spouse/family quality, and low network quality (Antonucci, Ajrouch, & Birditt, 2014;Birditt & Antonucci, 2007). Quality has been measured in a variety of ways, including the examination of support, companionship, and affection as positive relationship qualities, and demandingness, criticalness, conflict, and loneliness as negative (Antonucci et al, 2014;Birditt & Antonucci, 2007;Shiovitz-Ezra & Litwin, 2012).…”
mentioning
confidence: 99%